Frameworks analysis and evaluation used in the web-application development - Selivorstova, Yuliia Romanivna; Liutenko, Iryna Victorivna; Orekhov, Sergey Valerievich (Національний технічний університет "Харківський політехнічний інститут", 2020)
This article presents the approaches used to analyze and evaluate modern frameworks that are used in the development of web applications. The analysis and evaluation of frameworks allow you to choose the framework that can be most efficaciously used for each specific case of software development. The popularity of using frameworks in the development of web applications is due to a significant reduction in the time and other resources spent on project execution. The article describes the concept of a framework as a technology for developing web applications and the classification of frameworks. Five main types of frameworks are briefly described. Criteria for the rationality of using frameworks for developing a web application are considered. The advantages and disadvantages of using them when creating web-oriented software are given. When evaluating web applications according to COCOMO model, software options were considered with the use of frameworks in development, and without the use of frameworks. This article provides an overview of the families of modern Back-End frameworks. A comparison of the functionality of the Back-End frameworks of six manufacturers for commercial software solutions is carried out. The choice of criteria for assessing the quality of frameworks is examined. As a basis, when choosing quality criteria, it is proposed to use the ISO 25010 standard. The coefficients of importance for the evaluation criteria, the values of which were obtained with the help of experts, are given. When forming the final assessment of the frameworks, such characteristics as functional suitability, security of working with data, modifiability, interface quality, interaction with payment systems, and integration with JIRA, compatibility, productivity were mentioned. General quality scores were obtained for all the frameworks under consideration. Assessing the quality of frameworks allows you to improve the process of developing a web-oriented software product, the purpose of which is to obtain a web application of a given quality.

У даній статті представлені підходи, які використовуються для аналізу та оцінки сучасних фреймворків, які використовуються при розробці web-додатків. Аналіз і оцінка фреймворків дозволяє обрати фреймворк, який найбільш ефективно може бути використаний для кожного конкретного випадку розробки програмного забезпечення. Популярність використання фреймворків при розробці веб-додатків обумовлена істотним зменшенням витрат тимчасових і інших ресурсів на виконання проекту. У статті наведено поняття фреймворку, як технології розробки веб-додатків і класифікація фреймворків. Коротко охарактеризовані п'ять основних типів фреймворків. Розглядаються критерії раціональності використання фреймворків для розробки веб-додатки. Наводяться переваги і недоліки використання їх при створенні веб-орієнтованого програмного забезпечення. При оцінці веб-додатків по моделі COCOMO розглянуті варіанти програмного забезпечення з використанням фреймворків в розробці, і без використання фреймворків. У статті наведено огляд сімейств сучасних Back-End фреймворків. Проведено порівняння функціональності Back-End фреймворків шести виробників для комерційних програмних рішень. Розглянуто вибір критеріїв для оцінки якості фреймворків. В якості основи, при виборі критеріїв якості, запропоновано використовувати стандарт ISO 25010. Наведено коефіцієнти важливості для критеріїв оцінки, значення яких отримані за допомогою експертів. При формування підсумкової оцінки фреймворків розглядалися такі характеристики як функціональна придатність, безпека роботи з даними, можливість модифікування, якість інтерфейсу, інтеграція з платіжними системами і інтеграція з JIRA, сумісність, продуктивність. Отримано загальні оцінки якості для всіх розглянутих фреймворків. Проведення оцінки якості фреймворків дозволяє поліпшити процес розробки веб-орієнтованого програмного продукту, метою якого є отримання веб-додатку заданої якості.
Аналіз та оцінка фреймворків, що використовуються для розробки web-додатків
Keywords: quality assessment; assessment criteria; оцінка якості; критерії якості